A study on the characteristic and performance of cascade drain in Malaysia - Siti Nur Affizza , Md Yusuf (2013)
Cascade drain is one of the hydraulic structures that are widely used in slope condition area. The functions of cascade drain are to control and convey flows from surface runoff at upstream to downstream. The advantages of cascade drain are the simple, economic and rapid construction procedure plus the aforementioned economic savings. The aims of this study are to study the characteristic and performance of cascade drain for the working and the behaviour. There were three different types of cascade drain which are horizontal step, end sills step and inclined step. The dimensions of every cascade drain are recorded. The discharge values were calculated using Rational Method and been compared with the Manning's Equation. The drop length of water while raining was recorded and the Froude number were calculated to determine the hydraulic jump. From the comparison among three different types of cascade drain, the most sufficient cascade drain with the best jump is the horizontal step cascade drain. Horizontal step cascade drain provided a short length for each step that influence the distance ofjump;